(3TQM GdcaGjIs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg GdEeGQGJ gj GdCehQ GdebjOI ddXf, bhdg(B: (3GdeYJHQI TQYG cGdLRA GdhGMO MjK Ef GdTGQY CeVi GdYed Hg hcPG GdXGgQ bhdg Ch YbdG cGdXf GdeWdbs
(3BNQgG (B:s
(3BNQgG(B: (3hcdeI OGYjI Edjg Cj Edi fUHg hgPG YWa JaSjQ Ydi bhdg HedGc jhLH fUHg, bhdg dRhe GdEWGYI HfMh gh GdXf bhdg HfMh BNQs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg aj fgGjI GdLRA GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs